2021
DOI: 10.3389/fpls.2021.637236
|View full text |Cite
|
Sign up to set email alerts
|

Floral Longevity of Paphiopedilum and Cypripedium Is Associated With Floral Morphology

Abstract: Floral longevity (FL) is an important trait influencing plant reproductive success by affecting the chance of insect pollination. However, it is still unclear which factors affect FL, and whether FL is evolutionarily associated with structural traits. Since construction costs and water loss by transpiration play a role in leaf longevity, we speculated that floral structures may affect the maintenance and loss of water in flowers and, therefore, FL. Here, we investigated the slipper orchid Paphiopedilum and Cyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In fact, water supply and demand in leaves are primarily determined by minor leaf vein density (VLA) and stomatal density (SD), respectively ( Brodribb et al., 2017 ). Currently, many studies have observed a positive relationship between SD and VLA ( Carins Murphy et al., 2014 ; Brodribb et al., 2017 ; Lei et al., 2018 ), but negative or marginal correlation is also found in some cases ( Zhang et al., 2015 ; Zhang et al., 2021 ). Thus, there is still controversy over the direction of SD-VLA coordination and whether such coordination is a common feature.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, water supply and demand in leaves are primarily determined by minor leaf vein density (VLA) and stomatal density (SD), respectively ( Brodribb et al., 2017 ). Currently, many studies have observed a positive relationship between SD and VLA ( Carins Murphy et al., 2014 ; Brodribb et al., 2017 ; Lei et al., 2018 ), but negative or marginal correlation is also found in some cases ( Zhang et al., 2015 ; Zhang et al., 2021 ). Thus, there is still controversy over the direction of SD-VLA coordination and whether such coordination is a common feature.…”
Section: Introductionmentioning
confidence: 99%
“…Floral longevity is the length of duration that flowers remain open and functional, which is a key floral characteristic that impacts the reproductive fitness of plants (Primack, 1985 ). Floral longevity varies considerably from a day or less (e.g., Ipomoea purpurea ) up to 2 months (e.g., some species from Orchidaceae ) among flowering plants (Kerner von Marilaum, 1895 ; Gori, 1983 ; Primack, 1985 ; Ashman and Schoen, 1994 ; Zhang et al, 2017 , 2021 ). Some studies have indicated that the duration of the life history in leaves was correlated with genome size within vascular plants (Finch, 1990 ; Morgan and Westoby, 2005 ; Beaulieu et al, 2007 , 2008 ; Théroux-Rancourt et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study found a weak positive correlation between leaf lifespan, leaf mass per area, and genome size, suggesting that among angiosperms, genome size and leaf strategy are not related (Morgan and Westoby, 2005 ). Variation of floral longevity may imply different ecological strategies (Zhang et al, 2021 ). Therefore, understanding the genetic basis of variation in floral longevity is of great value.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations